Desulfitative C‐Arylation of Glycals by Using Benzenesulfonyl Chlorides1. Issue 3 (10th December 2014) - Kusunuru, Anil Kumar; Yousuf, Syed Khalid; Tatina, Madhubabu; Mukherjee, Debaraj
Abstract: The palladium‐catalyzed stereoselective synthesis of 2, 3‐deoxy‐ C ‐aryl glycosides was investigated. The strategy is based on the Pd‐catalyzed desulfitative Heck coupling of arylsulfonyl chlorides and glycals with good leaving groups. An attempt was made to establish the reaction mechanism, which may involve Pd II /Pd 0 interconversion under basic conditions. Abstract : A highly stereoselective desulfitative C ‐arylation reaction is developed by using glycal and arylsulfonyl chlorides in the presence of bis(triphenylphosphine)palladium(II) chloride and Li2 CO3 . A wide variety of glycals and arylsulfonyl chlorides participate in the reaction smoothly. C ‐Arylation happens possibly through a catalytic cycle involving Pd II /Pd 0 species.